Kartagener syndrome, current data on a classical disease. Case report. - Sandra Viviana Gómez-Correa; Iván David Ruiz-Ángel; Luis Carlos Salazar-Díaz (Case Reports)
Introduction: This article addresses the general aspects (pathophysiology, embryology, clinical presentation and prognosis) of the Kartagener syndrome (KS). Case presentation: 26-year-old male patient, with a history of complicated sinusitis with cerebral abscess and secondary epilepsy, who consulted to the Hospital Universitario Nacional de Colombia due to headache, fever and mucus expectoration. The presence of situs inversus, chronic sinusitis and bronchiectasis suggested a diagnosis of primary ciliary dyskinesia and KS. Discussion: Differential diagnoses of KS should be framed in its possible causal relationship with primary ciliary dyskinesia and other diagnoses associated with secondary ciliary dysfunction, such as cystic fibrosis, immunodeficiency and anatomical-functional conditions with rhinosenopulmonary involvement. Clinical suspicion of KS occurs when the heart is auscultated on the right and the liver is palpated on the left. Confirmation is achieved through imaging methods that prove visceral heterotaxia, indirect methods related to scan of ciliary malfunction (nasal nitric oxide, video microscopy) and ciliary biopsy that demonstrates the defect of the ciliary ultrastructure. Conclusions: Respiratory infectious involvement in patients with KS is explained by the alteration of the cilia, which leads both to the malposition of some organs and to the structural and functional alteration of others.